ANALISIS DAYA DUKUNG WISATA PANTAI MENGANTI KECAMATAN AYAH KABUPATEN KEBUMEN - Utami, Putri; Santoso, Apik Budi (Geo-Image, 2019)
Menganti Beach is a tourist destination for both local and outside tourists. The number of visits from year to year continues to increase, in 2016 the number of tourists was 227.530 while in 2017 the number of tourists was 448.667. The high interest of visitors to travel to Menganti Beach can cause environmental damage. Therefore it is necessary to study tourism carrying capacity to determine the maximum number of tourist visitors that can still be tolerated. The purpose of this study is Knowing the carrying capacity of Menganti Beach tourism.The data analysis used is descriptive and the calculation of support capacity using the Douglas method (1975) in Fandeli (2001) by calculating physical carrying capacity (PCC), real carrying capacity (RCC), and effective carrying capacity (ECC). Based on the calculating result obtained physical carrying capacity is 6.232, the real carrying capacity is 501, and the effective carrying capacity is a 351. So with the value of PCC > RCC > ECC, shows that tourism carrying capacity in Menganti Beach has not been exceeded. However, actually when the peak season, real carrying capacity and effective carrying capacity of Menganti Beach have excedeed with the number of visits a day is 6.000 tourist, and when low season the real carrying capacity has not been exceeded by 240 tourist.